Adaptive Dual-Comb Spectroscopy With 1200-h Continuous Operation Stability - Xuling Shen; Ming Yan; Qiang Hao; Kangwen Yang; Heping Zeng (IEEE Photonics Journal, 2018)
Dual-comb spectroscopy (DCS), without moving mirrors, enables fast optical sampling of molecular vibrations and results in high-resolution and high-accuracy Fourier-transform spectra. This motionless technique holds much promise in gas sensing and environmental monitoring. However, in many cases, these applications require a mature device continuously operating for days or even months, thus posing a challenge to long-term stability of this delicate technique. In this paper, we demonstrate the feasibility of DCS for long-term routine spectral monitoring. A compact dual-comb spectrometer is built based on adaptive sampling and simple frequency stabilization schemes. The spectrometer is ceaselessly recording and displaying, in real time, transmission spectra of a phase-shifted fiber Bragg grating and of gas-phase samples for over 1200 h (50 days). We spectroscopically validate the system by measuring absorption lines of ν1 + ν3 band of C2H2 and of 2ν 3 band of CH4 and comparing the experimental data with HITRAN database.